2D electrical resistance (ER) mapping to Detect damage for carbon fiber reinforced polyamide composites under tensile and flexure loading. (5th January 2021) - Kim, Jong-Hyun; Shin, Pyeong-Su; Kwon, Dong-Jun; Park, Joung-Man
Abstract: The carbon fiber reinforced thermoplastic composites (CFRTC) has been applied in the manufacture of automobiles. The in-situ damage sensing and nondestructive evaluation techniques are important in automobile industries. In this paper, the damage of Carbon fiber (CF)/Polyamide (PA) composite was sensed in-situ using electrical resistance (ER) on tensile and flexural stresses in specimens. The CF dispersion in CF/PA composite was evaluated using ER and calculated using an empirical formula. The CF/PA composite was manufactured with different CF weight fractions using an injection process. The load on specimens was sensed using the difference of ER as the tensile and flexural loads increased. The correlation between load and difference of ER was arranged using some equations. The CF array form was evaluated using ER at 1 cell area of the CF/PA composite. The sensing ability in the CF/PA composite was dependent on the weight fraction of CF because of bad dispersion of CF. The CF dispersion and damage sensing of real-products made of CF/PA composite can be evaluated using ER. The 20 wt% CF added PA composite was the optimal condition for evaluation of dispersion of CF and damage sensing using ER. Graphical abstract: Image 1